Financial Literacy ‘Not the Primary Problem’ for Australians who Forego Building, Home Contents and Comprehensive Car Insurance - Evgenia Bourova; Ian Ramsay; Paul Ali (Australasian Accounting Business and Finance Journal, 2024)
Financial literacy continues to receive attention in analyses of the drivers of noninsurance in Australia. Government advertising campaigns have been launched seeking to address an alleged lack of awareness of the benefits of building, home contents and comprehensive car insurance in the community. Yet there is inadequate research connecting insurance uptake decisions with financial literacy levels. In this article, we address this research gap by drawing upon surveys of ‘insured’ Australians with building, home contents and comprehensive car insurance; and ‘uninsured’ Australians without any of these insurance products. While our findings do not indicate a clear-cut relationship between financial literacy and noninsurance, they do show somewhat lower financial literacy and confidence levels among those who forego coverage. However, the question of whether investment in generalised financial literacy education would result in greater insurance uptake remains open. Ultimately, more information does not address the ‘primary problem’ of affordability, which renders insurance inaccessible to many Australians, particularly those on low incomes, despite their acknowledgment of its importance.
Keywords: financial literacy; insurance literacy; noninsurance; uninsured Australians; survey